EDUKASI KEAMANAN OBAT TRADISIONAL SISWA MANU 3 ITTIHAD BAHARI MELALUI CEK KLIK BPOM - Ainun Fawaid; Nisa Febrinasari; Nurul Isma; Dhara Retnaning Prameswari; Dwi Endah Kusumawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2026)
The circulation of traditional medicines without official distribution permits and containing hazardous materials is a serious problem in society, including among students. Low literacy on how to select and verify the safety of traditional medicines makes adolescents vulnerable to using unsafe products. Therefore, it is important to provide education from an early age on simple ways to check the legality and safety of medicines, one of which is through the Cek KLIK BPOM program (Check: Packaging, Label, Distribution Permit, and Expiration Date). This community service activity aims to increase the understanding and awareness of students at MA NU 3 Ittihad Bahari Purworejo Bonang Demak regarding the importance of being smart consumers in choosing traditional medicines. The specific target is for students to be able to recognize the characteristics of safe traditional medicines, use the online Cek BPOM feature, and develop a critical attitude in selecting and using medicines. The methods used include interactive counseling to deliver the material, simulations using the BPOM website application, question and answer discussions to deepen understanding, and pre-posttest evaluations to measure the increase in student knowledge. The pre-test scores (13.4%) and post-test scores (54.4%) indicated an increase in knowledge about traditional medicine safety education through BPOM's KLIK Check. This is an initial step in developing a young generation that is aware of the importance of health and the safety of the products they consume.